Reducing CO2 Emissions through Biogas, Wind and Solar Energy Production: Evidence from Indonesia - Yuaningsih, Lilis; Febrianti, R. Adjeng Mariana; Kamran, Hafiz Waqas (International Journal of Energy Economics and Policy, 2020)
CO2 emission has become a growing concern for most of the countries and many factors or reasons have been found to enhance this emission in one way or the other. In this particular study, the impact of biogas energy, wind energy and solar energy production is supposed to be studied on CO2 emission in Indonesia. The author has collected data for research purpose from Indonesia. The data covers the period of 29 years and has been collected from authentic databases. After data collection process, several tests and techniques are used for the purpose of analyzing and exploring various aspects related to the study and the variables. The tests used by the author in this study include unit root test and GMM estimation technique. All these tests have distinct features and used for various purposes. The results obtained from the above-mentioned tests indicate that the production of all types of energies discussed in the study i.e. biogas, wind and solar energy have significant impacts on CO2 emission while the impact of the only control variable, energy consumption is found to be insignificant. Various theoretical, practical and policy making implications have been identified by the author and some limitations of the study have also been discussed in the last. Keywords: CO2 Emissions, Wind Energy, Solar Energy JEL Classification: Q13 DOI: https://doi.org/10.32479/ijeep.10590